2023
DOI: 10.1002/uog.26096
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of stillbirth: effect of deprivation

Abstract: Objectives To examine the relationship between the English index of multiple deprivation (IMD) and the incidence of stillbirth and assess whether IMD contributes to the prediction of stillbirth provided by the combination of maternal demographic characteristics and elements of medical history. Methods This was a prospective, observational study of 159 125 women with a singleton pregnancy who attended their first routine hospital visit at 11 + 0 to 13 + 6 weeks' gestation in two maternity hospitals in the UK. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…However, the authors demonstrated that incorporating IMD quintiles into screening algorithms did not improve the prediction of pre-eclampsia or stillbirth. It is of note that in the latter study, only 15% of women were of black origin, whereas 47% were from the most socioeconomically deprived areas (IMD quintiles 1 and 2) 3 .…”
Section: Comparison With Existing Literaturementioning
confidence: 62%
See 4 more Smart Citations
“…However, the authors demonstrated that incorporating IMD quintiles into screening algorithms did not improve the prediction of pre-eclampsia or stillbirth. It is of note that in the latter study, only 15% of women were of black origin, whereas 47% were from the most socioeconomically deprived areas (IMD quintiles 1 and 2) 3 .…”
Section: Comparison With Existing Literaturementioning
confidence: 62%
“…The most deprived areas were allocated to the lowest group (Group 1), while the least deprived were in the highest group (Group 10). IMD indices have been used extensively in the literature as a proxy for socioeconomic deprivation 3,9,13 , and are periodically updated 8 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations